Multimodal Texts in Chilean English Teaching Education: Experiences from Educators and Pre-Service Teachers [Textos Multimodales en la Formación Docente en Inglés en Chile: Experiencias de Formadores y Estudiantes de Licenciatura] - Farias-Farias, M (Universidad Nacional de Colombia, 2019)
Drawing on 10 pedagogical standards issued by the Chilean Ministry of Education, three dealing with multimodality, we, in this research, examined English language pre-service teachers’ and educators’ approaches to the use of multimodal texts. Data were gathered through two online surveys that explored the use of multimodal texts by teacher educators and pre-service teachers. Results indicate that educators were familiar with the standards and multimodality when teaching reading and writing, but lack of resources, preparation, and time prevents them from working with multimodal texts. Candidates read printed and digital newspapers, novels, and magazines outside university, but rarely use them academically. They extensively use social media, even for academic purposes. There is a mismatch between the use of multimodal texts by teacher candidates and teacher educators. © 2019, Universidad Nacional de Colombia. All rights reserved.